Classifying technology policy from an evolutionary perspective - Uwe Cantner; Andreas Pyka (Universität Augsburg, Institut für Volkswirtschaftslehre, 1999)
Asked for the most important driving forces of economic development, most economists do not hesitate to state, that it is technical progress which is the main source of quanti-ta-ti-ve and qualitative economic development generated in National Systems of Innovation (NSI). To classify and analyze NSI's the con-cepts of mission- and diffusion-oriented policy designs were introduced. Although, we suppose this taxonomy to be well suited to analyze techno-logy policy, it seems to us in its basic formulation somewhat crude, especially with respect to the supposed characteristics to assign a specific innovation system to the one or the other policy design. To surmount these shortcomings we develop a new classificatory scheme building on a questionnaire approach and suggesting four categories to spread out between the tech-nology and the economic side. This scheme allows for deeper insights and more evident com-pa-risons of different NSI's.
urn:nbn:de:bvb:384-opus4-276823
Keywords: O39; 330